The changing political landscape of Sweden: Political cleavages, actors and processes (Sociologisk Forskning, 2018)
The political landscape in Sweden has undergone considerable changes in recent decades The number of political parties in the Swedish parliament has increased from five to eight, and the socio-economic issues of the traditional political right–left scale has been challenged by socio-cultural issues relating to lifestyle and identity. Notably, the notion of Swedish exceptionalism and the particularities of its welfare state is lingering despite findings pointing in the opposite direction e.g. with the increased electoral support for the radical right, and its ethno-nationalist and anti-immigrant rhetoric. The corporatist model has been challenged by new forms of political authority, participation and representation. New political actors, such as social movements and civil society actors, think tanks and policy professionals, are becoming increasingly engaged in political processes. The long-term trend suggests that traditionally marginalised groups, such as the young, women and groups of migrant background, are represented in decision-making forums to a higher degree than before. Yet, current conditions need further analysis. In this article, we provide a background to Sociologisk Forskning’s special issue on the political landscape of the parliamentary election in 2018.
Keywords: cleavages; political sociology; radical rightwing parties; the Sweden Democrats; Swedish Exceptionalism and the Swedish general election 2018